Enzyme-induced calcium carbonate precipitation treated loess fly ash-based geopolymer for airport slope stabilization: Evaluation of wetting deformation and vibratory disintegration - Jiulong Gao; Jiading Wang; Dengfei Zhang; Fei Wang; Lirong Qi (Case Studies in Construction Materials)
This study explores the feasibility of using enzyme-induced carbonate precipitation (EICP) to produce loess fly ash-based geopolymer (LFG) as a grouting material for fissures in airport slopes. The effects of mixture proportions and cementation levels on the engineering properties, water absorption, and calcium carbonate content were evaluated. Laboratory tests, including modified unsaturated triaxial and vibratory disintegration tests, were conducted to simulate complex environmental factors such as rainfall, vibration, and stress history on grouted slopes. The results demonstrated that an optimized EICP formula enhanced the shear strength of LFG by 17 %–35 % and improved its resistance to deformation. The decrease in the sorptivity coefficient, negatively correlated with calcium carbonate content, was under 10 %. Wetting-induced deformation was minimized as the cementation level of LFG increased under deviatoric stress. Based on the wetting test, the “Iw” control parameter was proposed to quantify the resistance of grouted geopolymer materials to water-induced failure in loess landslide stabilization. The vibratory disintegration tests showed that the appropriate EICP formula reduced the water erodibility of LFG, thus improving its resistance to disintegration with a maximum index of 77.65 %. However, vibration decreased the disintegration resistance index, particularly at resonance (f = 20 Hz). Microscopic analysis revealed that the shape of the precipitated calcium carbonate crystals influenced the hydromechanical properties of LFG, with rhombic crystals exhibiting better performance.